2014
DOI: 10.1037/cep0000014
|View full text |Cite
|
Sign up to set email alerts
|

Will your words become mine? Underlying processes and cowitness intimacy in the memory conformity paradigm.

Abstract: Eyewitness reports become less accurate after exposure to inconsistent information. When such phenomenon of diminishing accuracy occurs among cowitnesses, it is termed memory conformity or the social contagion effect. The present study set out to provide a rigorous test of the underlying mechanisms with particular emphasis on investigating whether genuine false memory is involved. To this end, we conducted an earwitness experiment in which some participants were exposed to discrepant cowitness information and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 46 publications
0
12
0
5
Order By: Relevance
“…The effect of social influence was still present, however. Many other studies confirmed that misinformation delivered in a social interaction is effective (e.g., Dalton & Daneman, 2006;Gabbert et al, 2003;Hewitt, Kane, & Garry, 2013;Luus & Wells, 1994;Mudd & Govern, 2004;Numbers, Meade, & Perga, 2014;Oeberst & Seidemann, 2014;Schneider & Watkins, 1996;Wright et al, 2000).…”
mentioning
confidence: 86%
“…The effect of social influence was still present, however. Many other studies confirmed that misinformation delivered in a social interaction is effective (e.g., Dalton & Daneman, 2006;Gabbert et al, 2003;Hewitt, Kane, & Garry, 2013;Luus & Wells, 1994;Mudd & Govern, 2004;Numbers, Meade, & Perga, 2014;Oeberst & Seidemann, 2014;Schneider & Watkins, 1996;Wright et al, 2000).…”
mentioning
confidence: 86%
“…A similar problem was investigated by Oeberst and Seidemann (2014). They found that it was mainly informational influence that was responsible for memory conformity.…”
mentioning
confidence: 87%
“…Normative influence is most often observed when participants are tested together and responses are given publicly rather than privately and when costs of disagreeing are high (see Allan & Gabbert, ; Schneider & Watkins, ; Shaw, Garven, & Wood, ). For example, memory conformity effects are typically larger when witnesses know each other, with participants more likely to report information acquired from a friend or romantic partner than from a stranger (French, Garry, & Mori, ; Hope, Ost, Gabbert, Healey, & Lenton, ; but see Oeberst & Seidemann, ), and from an in‐group than from an out‐group partner (Andrews & Rapp, ). Similarly, Wheeler, Allan, Tsivilis, Martin, and Gabbert () observed an enhanced conformity effect towards “similar others” on a collaborative memory task.…”
Section: Remembering With Others In Eyewitness Contextsmentioning
confidence: 99%